1978
DOI: 10.1111/j.1365-2990.1978.tb00544.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Serum Proteins in Cerebral Gliomas and Metastatic Tumours: An Immunoperoxidase Study

Abstract: An immunoperoxidase technique was used to compare the presence of serum proteins in tumour cells in twenty cerebral gliomas and four intracerebral metastatic carcinomas, with the serum protein content of reactive astrocytes around four cerebral infarcts. Rabbit antiserum to human immunoglobulins and albumen was applied to paraffin sections of tumour biopsies and of infarcts from postmortem brains. All the reactive astrocytes surrounding infarcts stained positively for immunoglobulins and albumen. In the glioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

1981
1981
2006
2006

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 16 publications
0
2
1
Order By: Relevance
“…The 1-3 mm pores of gelatin-coated filters recapitulated gaps in tissue. Although others have demonstrated selective accumulation of serum albumin in astrocytomas 5,6 and to some extent on glioma cells, 4,16 this study demonstrated preferential accumulation of albumin on or in pseudopodia of astrocytoma cells using gels, immunoblots, and fluorescent labeling. Protein bands that were increased in pseudopodial lysates on 1D electrophoretic gels were confirmed to be BSA with MS. On immunoblots, with lysate loading equalized for levels of GAPDH, BSA was increased to levels comparable or greater than those of known pseudo-podial proteins, b-actin and ezrin.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…The 1-3 mm pores of gelatin-coated filters recapitulated gaps in tissue. Although others have demonstrated selective accumulation of serum albumin in astrocytomas 5,6 and to some extent on glioma cells, 4,16 this study demonstrated preferential accumulation of albumin on or in pseudopodia of astrocytoma cells using gels, immunoblots, and fluorescent labeling. Protein bands that were increased in pseudopodial lysates on 1D electrophoretic gels were confirmed to be BSA with MS. On immunoblots, with lysate loading equalized for levels of GAPDH, BSA was increased to levels comparable or greater than those of known pseudo-podial proteins, b-actin and ezrin.…”
Section: Discussioncontrasting
confidence: 54%
“…increased permeability of the BBB in these tumors, 31,32 possibly aided by the ability of astrocytic cells to ingest albumin. 4,16 Albumin has a large capacity and high affinity for fatty acids so that the pool of circulating HSA in the bloodstream quantitatively forms an important source of lipids for delivery to tumor cells, with or without the aid of various fatty acid-binding proteins in the recipient cells. 33 Patterns and rates of fatty acid incorporation by glial cells have been found to vary according to the degree of cellular differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation